Verifying liveness by multiple experts in face biometrics - Kollreider, K.; Fronthaler, H.; Bigun, J. (2008 IEEE Computer Society Conference on Computer Vision and Pattern Recognition Workshops, 2008)
Resisting spoofing attempts via photographs and video playbacks is a vital issue for the success of face biometrics. Yet, the ldquolivenessrdquo topic has only been partially studied in the past. In this paper we are suggesting a holistic liveness detection paradigm that collaborates with standard techniques in 2D face biometrics. The experiments show that many attacks are avertible via a combination of anti-spoofing measures. We have investigated the topic using real-time techniques and applied them to real-life spoofing scenarios in an indoor, yet uncontrolled environment.